Magnetorheological Fluid Filled Spring for Variable Stiffness and Damping: Current and Potential Performance - Sikulskyi, Stanislav; Malik, Aryslan; Kim, Daewon (Frontiers in Materials, 2022)
Magnetorheological (MR) fluid is a smart material utilized for semi-active damping devices thanks to its ability to become viscoelastic solid under a magnetic field and provide variable damping. While most of these devices primarily utilize the fluid’s drastic increase in viscosity, its variable stiffness is rarely utilized. A MR fluid filled spring is a novel device with variable stiffness and damping and is the subject of the present study. First, the derived analytical model and the device’s controllable stiffness capability were experimentally validated by performing tensile tests with a fabricated hollow polymer spring filled with MRF-132DG. The analytical model was proved to describe the MR fluid static effect of increased spring stiffness accurately. Secondly, dynamic testing demonstrated the device’s controllable damping and capability to shift natural frequencies. In addition, the testing unveiled an enhanced dynamic performance of the spring due to the cumulative effect of MR fluid activation and specifically aligned uniform magnetic field. Finally, the hollow spring design was optimized through analytical and non-linear finite element buckling analysis to maximize MR fluid stiffness effect. The resulting critical parameters of the optimized design were used to estimate the effects of hollow spring material and operating conditions on the variable stiffness of the device.